2016
DOI: 10.1542/peds.2015-4635
|View full text |Cite
|
Sign up to set email alerts
|

Sports- and Recreation-Related Concussions in US Youth

Abstract: The incidence of sports-and recreation-related concussions (SRRCs) in the United States is unknown. More than 44 million youth participate in sports annually, thus understanding the frequency of SRRCs in children is important on a population level. Our objective was to determine the number of SRRCs occurring annually among US youth ≤18 years old. METHODS:We identified SRRCs using 3 national databases: MarketScan, National Electronic Injury Surveillance System, and National High School Sports Related Injury Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
235
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(243 citation statements)
references
References 27 publications
1
235
1
Order By: Relevance
“…A cross-sectional survey by Register-Mihalik et al (2013), using a convenience sample of high school athletes from nine different states, found that more than half (53%) of athletes recalled sustaining at least one possible concussion. Using existing databases, Bryan, Rowhani-Rahbar, Comstock, Rivara, et al (2016) estimated the annual incidence of sports- and recreation-related concussion among youth ages 18 and younger and found that between 1.1 and 1.9 million occurred each year.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey by Register-Mihalik et al (2013), using a convenience sample of high school athletes from nine different states, found that more than half (53%) of athletes recalled sustaining at least one possible concussion. Using existing databases, Bryan, Rowhani-Rahbar, Comstock, Rivara, et al (2016) estimated the annual incidence of sports- and recreation-related concussion among youth ages 18 and younger and found that between 1.1 and 1.9 million occurred each year.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report using data from emergency room visits, office visits and a high school injury surveillance system estimated 1.0–1.8 million SRCs per year in the 0–18 years age range and a subset of about 400 000 SRCs in high school athletes 11. While this estimate is likely accurate, determining actual sport-based or activity-based concussion rates is difficult.…”
Section: Epidemiologymentioning
confidence: 99%
“…Seasonal or annual risk may be a more readily understood concept. It is estimated that over 50% of concussions in high school-aged youth are not related to organised sports and only 20% are related to organised school team sports 11. Between 2% and 15% of athletes participating in organised sports will suffer a concussion during one season12–29 (table 2).…”
Section: Epidemiologymentioning
confidence: 99%
“…In the United States, there were 1.1 million football players, 36,000 ice hockey players and a total of over 7.8 million high school sport athletes in (NFHS 2016. Bryan et al (2016) estimated between 1.1-1.9 million sport-related and recreation-related concussions occur annually in those ≤18 years of age. This large range is due to the majority of US youth who likely sustained a concussion but were not examined by a qualified professional and thus, were not accurately diagnosed (Bryan et al 2016).…”
Section: Introductionmentioning
confidence: 99%